2014
DOI: 10.5812/ircmj.17056
|View full text |Cite
|
Sign up to set email alerts
|

Fibronectin Regulation by Vitamin C Treatment in Kidneys of Nicotinic Mice Offspring

Abstract: Background:Maternal cigarette smoking causes health risks and developmental defects in the offspring. So far, many studies have been conducted to suppress the effects of nicotine. However, the effects of coadministration of vitamin C and nicotine on extracellular matrix have not gained enough attention.Objectives:This study decided to investigate the effects of vitamin C on fibronectin expression in kidneys of mice offspring, treated with nicotine.Materials and Methods:Eighteen female pregnant BALB/c mice were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 32 publications
(40 reference statements)
1
6
0
Order By: Relevance
“…Previous researchers found that abnormal nuclear shape is associated with premature and normal aging, as well as cancer [41] [42] [43]. The changes observed in the kidney are greatly improved by the use of vitamin C. Consistent with our results; one study revealed that vitamin C antagonized nicotine-induced kidney damage through reduction of fibronectin accumulation in proximal tubules of the kidney [44].…”
Section: Discussionsupporting
confidence: 81%
“…Previous researchers found that abnormal nuclear shape is associated with premature and normal aging, as well as cancer [41] [42] [43]. The changes observed in the kidney are greatly improved by the use of vitamin C. Consistent with our results; one study revealed that vitamin C antagonized nicotine-induced kidney damage through reduction of fibronectin accumulation in proximal tubules of the kidney [44].…”
Section: Discussionsupporting
confidence: 81%
“…Total RNA Extraction: The testicular tissue that had been stored in RNA-later solution at -70°C, was thawed at room temp and underwent the following steps according to the RNA extraction kit protocol [12].…”
Section: Real-time Pcr Techniquementioning
confidence: 99%
“…cDNA Synthesis: The cDNA was synthesized as per the instructions and protocol provided by the cDNA Synthesis Easy Kit manufacturer [12]. In the first stage, 5 µL of total RNA, 2 µL of Oligo-dt and 1 µL of Random hexamer were mixed in a microtube.…”
Section: Real-time Pcr Techniquementioning
confidence: 99%
See 2 more Smart Citations